2023
DOI: 10.1007/s00417-023-06217-8
|View full text |Cite
|
Sign up to set email alerts
|

A mini-invasive surgical technique for Carlevale IOL implantation: case series study and description of concomitant surgery

Carla Danese,
Francesco Di Bin,
Paolo Lanzetta

Abstract: Purpose To examine the feasibility and outcomes of a modified technique for the implantation of scleral fixated Carlevale intraocular lens (IOL) (I71 FIL SSF. Soleko IOL Division, Pontecorvo, Italy), and to analyze the occurrence of adverse events. Methods This is a retrospective observational study conducted revising patients charts from 2018 to 2023. Thirty-five eyes of 33 patients were included. Patients requiring IOL explantation had either IOL disloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…All the authors reported an improvement in the best corrected visual acuity (BCVA) [ 1 , 20 , 21 , 22 , 24 , 25 , 30 , 32 , 34 , 38 , 44 , 45 ] ( Table 1 ), and in comparison to the Artisan iris claw lens (Artisan Aphakia IOL model 205, Ophtec BV, Gro-ningen, The Netherlands), no significant difference ( p = 0.19) was highlighted [ 26 , 29 , 36 ]. Some authors did not consider the refractive and/or visual outcomes [ 27 , 28 , 38 , 43 ] while other authors reported only post-operative visual data [ 8 , 9 , 26 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the authors reported an improvement in the best corrected visual acuity (BCVA) [ 1 , 20 , 21 , 22 , 24 , 25 , 30 , 32 , 34 , 38 , 44 , 45 ] ( Table 1 ), and in comparison to the Artisan iris claw lens (Artisan Aphakia IOL model 205, Ophtec BV, Gro-ningen, The Netherlands), no significant difference ( p = 0.19) was highlighted [ 26 , 29 , 36 ]. Some authors did not consider the refractive and/or visual outcomes [ 27 , 28 , 38 , 43 ] while other authors reported only post-operative visual data [ 8 , 9 , 26 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding corneal astigmatism ( Table 3 ), some authors did not show any changes from the pre-operative to the postoperative time [ 21 , 28 , 36 , 44 ]. Mularoni and colleagues [ 32 ] reported a small increase between pre-operative and post-operative astigmatisms.…”
Section: Resultsmentioning
confidence: 99%